Pengaruh Perubahan Arus Kas Dan Laba Akuntansi Terhadap Return Saham Pada Perusahaan LQ-45 Yang Terdaftar Di BEI Tahun 2017-2019 - Nur Faidah; M. Agus Salim; Ety Saraswati (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
ABSTARCTThis study aims to determine the effect of changes in operating cash flow and accounting profit partially and simultaneously on stock returns in LQ-45 companies listed on the stock exchange in 2071-2019. The method used is purposive sampling with a population of 45 companies and the sample used is 15 company data. Data analysis uses multiple linear regression. The result of this study indicate that partally operating cash flow has a positive and not significant effect on stock return on LQ-45 companies on the Stock Exchange in 2017-2019 and accounting profit have a positive and not significant effect on Stock Exchange in 20117-2019. Keywords : Operating Cash Flow, Accounting Profit And Stock Return